2014
DOI: 10.1111/ejh.12287
|View full text |Cite
|
Sign up to set email alerts
|

Similar outcomes of peripheral blood stem cells vs. bone marrow for human leukocyte antigen‐matched unrelated donor transplantation in adult patients with acute myeloid leukemia using risk‐adapted graft‐versus‐host disease prophylaxis

Abstract: Our risk-adapted GVHD prophylaxis strategy resulted in similar transplant outcomes including comparable incidence of GVHD between the PBSC and BM groups in HLA-matched URD-SCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…Which is not in accordance with the results of transplantations that were performed under a HLAidentical sibling setting [7,8,28]. And our conclusions were supported by other previous published studies [14,15,23]. On the contrary, other studies reported higher incidence of acute and chronic GVHD [14,16,29].…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Which is not in accordance with the results of transplantations that were performed under a HLAidentical sibling setting [7,8,28]. And our conclusions were supported by other previous published studies [14,15,23]. On the contrary, other studies reported higher incidence of acute and chronic GVHD [14,16,29].…”
Section: Discussioncontrasting
confidence: 52%
“…Several studies proved that the increased risk of GVHD could be controlled by transplantation protocols; an example is the use of risk-adapted GVHD prophylaxis [23], partial T-cell depletion or BM combined with PB as the source of stem cells [38,39]. The conclusion of our meta-analysis has some limitations because the included studies were not randomized and controlled.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In 2013, the primary results from BMT CTN0201 were published demonstrating comparable survival at 2 years for those randomized to PB and BM [2]. The failure to show a survival benefit in this trial as well as previous retrospective analyses [12][13][14][15][16][17][18][19] may have contributed to PB remaining the predominant graft source in roughly 80% of all URD recipients despite significantly higher rates of cGVHD and the need for prolonged immunosuppressants [1]. More recently published long-term patient-reported quality of life (QoL) data from the BMT CTN 0201 trial showed that at 5-years post-HCT, BM recipients reported significantly better QoL and were more likely to have returned to work compared with PB recipients; however, survival remained equivalent at 5 years [3].…”
Section: Discussionmentioning
confidence: 69%
“…The only significant difference was reported in chronic myeloid leukemia patients due to higher nonrelapse mortality rates in PB transplants [27]. In a Korean study, the difference in GVHD incidence could be overcomed by risk adapted GVHD prophylaxis in AML patients [28]. In aplastic anemia patients, the risk of death was higher with unrelated donors, but peripheral blood as a stem cell source was a negative predictor for outcomes [29].…”
Section: Peripheral Blood Versus Bone Marrowmentioning
confidence: 99%